2012
DOI: 10.1016/j.bpj.2012.02.018
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein-ATPase Modulation: The Molecular Mechanisms

Abstract: P-glycoprotein-ATPase is an efflux transporter of broad specificity that counteracts passive allocrit influx. Understanding the rate of allocrit transport therefore matters. Generally, the rates of allocrit transport and ATP hydrolysis decrease exponentially with increasing allocrit affinity to the transporter. Here we report unexpectedly strong down-modulation of the P-glycoprotein-ATPase by certain detergents. To elucidate the underlying mechanism, we chose 34 electrically neutral and cationic detergents wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(120 citation statements)
references
References 37 publications
11
108
0
1
Order By: Relevance
“…3, panel D. Interestingly, of the three Hoechst dyes tested, only H 33342 was transported. Recent studies showed that a certain balance between the hydrophobic and hydrophilic forces in the structure of the target substrate is essential for optimum efflux by Pgp (39). Because H 33342 is the most amphiphilic of the three dyes, this may explain why DrrAB is able to preferentially transport H 33342 but not the other two dyes.…”
Section: Drrab-mediated Dox Efflux Is Inhibited Bymentioning
confidence: 99%
“…3, panel D. Interestingly, of the three Hoechst dyes tested, only H 33342 was transported. Recent studies showed that a certain balance between the hydrophobic and hydrophilic forces in the structure of the target substrate is essential for optimum efflux by Pgp (39). Because H 33342 is the most amphiphilic of the three dyes, this may explain why DrrAB is able to preferentially transport H 33342 but not the other two dyes.…”
Section: Drrab-mediated Dox Efflux Is Inhibited Bymentioning
confidence: 99%
“…The open state can also be prolonged by binding of potentiators that reduce the ATPase activity and slow down flopping and drug release (rate constant k 2 ). As shown for P-glycoprotein, drug release is rate-determining (88).…”
Section: Discussionmentioning
confidence: 97%
“…Since overexpression of some of the ABC transporters was correlated with a poor chemotherapeutic response and prognosis of patients with specific cancer types, inhibition of ABC transporters appears a logical approach to circumvent MDR and improve patient's outcome [82,83] . However, other than in a preclinical setting where ABC transporters could reverse MDR, this promise has still not been fulfilled in clinical practice.…”
Section: Abc Transporter Inhibitionmentioning
confidence: 99%
“…Competitive inhibitors exert their function by tightly binding and blocking the substrate binding pockets. Non-competitive inhibitors exert their function by binding to a non-substrate binding site thereby inhibiting the ATPase activity or modulating transporters' function allosterically [15,[83][84][85] . Another strategy to circumvent MDR that will be discussed further is the application of small interfering RNA (siRNA) [86][87][88] and microRNA (miRNA) [89,90] inoculation to down-regulate ABC transporter expression.…”
Section: Abc Transporter Inhibitionmentioning
confidence: 99%